2006
DOI: 10.1083/jcb.200604046
|View full text |Cite
|
Sign up to set email alerts
|

EPI64 regulates microvillar subdomains and structure

Abstract: EPI64 is a TBC domain–containing protein that binds the PDZ domains of EBP50, which binds ezrin, a major actin-binding protein of microvilli. High-resolution light microscopy revealed that ezrin and EBP50 localize exclusively to the membrane-surrounded region of microvilli, whereas EPI64 localizes to variable regions in the structures. Overexpressing EPI64 results in its and EBP50's relocalization to the base of microvilli, including to the actin rootlet devoid of ezrin or plasma membrane. Uncoupling EPI64's b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
135
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(143 citation statements)
references
References 54 publications
5
135
0
Order By: Relevance
“…Second, a close comparative examination revealed distinct localizations of phospho-ERM and F-actin in different subdomains of single dendritic filopodia: phospho-ERM proteins are mainly localized in the distal portion of dendritic filopodia, whereas F-actin is more abundantly present in the proximal portion. Recently, a similar observation has been reported in differential localization of phospho-ERM and F-actin in subdomains of microvilli (Hanono et al, 2006). Because the distal portion of dendritic filopodia and microvilli are considered to be highly dynamic, the activated ERM may be involved in either polymerization or depolymerization of F-actin, leading to elongation or retraction of dendritic filopodia.…”
Section: Erm Proteins In Dendritic Filopodiamentioning
confidence: 62%
“…Second, a close comparative examination revealed distinct localizations of phospho-ERM and F-actin in different subdomains of single dendritic filopodia: phospho-ERM proteins are mainly localized in the distal portion of dendritic filopodia, whereas F-actin is more abundantly present in the proximal portion. Recently, a similar observation has been reported in differential localization of phospho-ERM and F-actin in subdomains of microvilli (Hanono et al, 2006). Because the distal portion of dendritic filopodia and microvilli are considered to be highly dynamic, the activated ERM may be involved in either polymerization or depolymerization of F-actin, leading to elongation or retraction of dendritic filopodia.…”
Section: Erm Proteins In Dendritic Filopodiamentioning
confidence: 62%
“…Indeed, an electron tomography study of the membrane skeleton reveals that the actin filaments are closely associated with the cytoplasmic surface of the plasma membrane within 10.2 nm (89). Ezrin and NHERF1 are distributed along almost the entire microvillus structure (14). The growing F-actin filaments can have intimate interactions with the lipid membrane and support the expanding cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Given that active Arf6 binds the Rab35 GAPs TBC1D10A (Hanono et al, 2006), TBC1D10B (Chesneau et al, 2012), and TBC1D24/Skywalker (Uytterhoeven et al, 2011), it seems highly likely that the ability of receptor tyrosine kinases such as EGF, human growth hormone and VEGF receptors to activate Arf6 leading to removal of cell surface cadherins (Palacios et al, 2001;Lu et al, 2003;Morishige et al, 2008;Sabe et al, 2009;Ji et al, 2009;Hashimoto et al, 2011) is mediated through inhibition of Rab35 activity. Moreover, active Arf6 inhibits MHC class I recycling (Caplan et al, 2002;Naslavsky et al, 2004) and we previously demonstrated that knock down of Rab35 inhibits efficient MHC class I recycling (Allaire et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent studies have demonstrated an intimate relationship between Rab35 and Arf6. Specifically, Arf6 binds the Rab35 GAPs TBC1D10A (Hanono et al, 2006), TBC1D10B (Chesneau et al, 2012) and TBC1D24/ Skywalker (Uytterhoeven et al, 2011), and expression of constitutively active Arf6 leads to defects in cytokineses and the accumulation of binucleated cells due to Arf6-mediated inhibition of Rab35 (Chesneau et al, 2012). Based on these observations, Arf6 has been placed upstream of Rab35.…”
Section: Introductionmentioning
confidence: 99%